5G, Religion, and Misconceptions in Communication during Covid-19 in Nigeria - Ndinojuo, Ben-Collins Emeka (Jurnal The Messenger, 2020)
5G was test-launched in Nigeria in 2019 to improve its communication technology, conspiracy theorists, however, linked 5G to the outbreak of the Covid-19. As with conspiracies, the who that lends credence to it affects how far it travels. Pastor Chris Oyakhilome, founder of Believers LoveWorld, added his voice to the 5G debate, claiming that Covid-19 lockdown was decoy to sequester the population for government to covertly deploy 5G. This study is important because it addresses the issue of fake news and its ability to cause civil disobedience in the society. Using secondary research method, content analysis was used to review arguments on 5G controversy in the Nigerian context. Findings revealed that government appealed for calm and stated that no license for the installation of 5G has been issued yet. Technology enthusiasts and media organizations put out fact-checking information in support of the technology. Various arguments indicate that no one really understands the full capabilities of 5G and its long-term effect on living organisms and the environment. It is recommended that more tests be carried out in varying conditions to understand the tolerance limit of the technology, and for the government to be transparent in its public communication.